THE EFFECTIVENESS OF USING THINK-TALK-WRITE (TTW) STRATEGY TO IMPROVE STUDENTS' ABILITY IN WRITING DESCRIPTIVE TEXT : A Quasi-experimental Study at One Junior High School - Dewi Rosiana, - (2018)
This study examines the effectiveness of using Think-Talk-Write strategy in improving students' ability in writing descriptive text. The purpose of this study is to find out whether the use of Think-Talk-Write strategy is effective to improve students' ability in writing descriptive text or not. Also, it intends to see the students' responses toward the use of Think-Talk-Write strategy in teaching descriptive text. The design used is the quasi-experimental design involving sixty students of Grade VII at one public junior high school in Bogor as the sample of this research. The instruments used are pre-test, posttest and the questionnaire of the effectiveness of Think-Talk-Write strategy. The results reveal that there is an improvement on students' writing in the experimental group after receiving treatment. Furthermore, the findings from questionnaire show that most students tend to respond positively toward the use of Think-Talk-Write strategy. They considered Think-Talk-Write strategy can improve their writing ability, make them easily tell their thought without being afraid of making mistake; help them in comprehending descriptive text material; and improve their grammar mastery. As a result, it can be concluded that the use of Think-Talk-Write strategy is effective in improving students' ability in writing descriptive text.;-- Penelitian ini menguji efektivitas penggunaan strategi Think-Talk-Write dalam meningkatkan kemampuan siswa dalam menulis teks deskriptif. Tujuan dari penelitian ini adalah untuk mengetahui apakah penggunaan strategi Think-Talk-Write dalam meningkatkan kemampuan siswa dalam menulis teks deskriptif efektif atau tidak. Penelitian ini juga dimaksudkan untuk mengetahui respon siswa terhadap penggunaan strategi Think-Talk-Write dalam pembelajaran teks deskriptif. Desain penelitian yang digunakan adalah penelitian percobaan semu yang melibatkan 60 siswa kelas VII di sebuah SMP Negeri di Bogor sebagai sampel penelitian. Instrument yang digunakan dalam penelitian ini adalah pretest, posttest dan angket efektivitas strategi Think-Talk-Write. Hasil dari penelitian menunjukkan adanya kemajuan antara tulisan siswa dalam kelompok percobaan setelah menerima perlakuan. Lebih jauh lagi, temuan dari angket menunjukkan bahwa sebagian besar siswa merespon positif terhadap penggunaan strategi Think-Talk-Write. Siswa-siswa menilai bahwa strategi Think-Talk-Write dapat meningkatkan kemampuan menulis mereka, membuat mereka dengan mudah memberitahukan pemikiran mereka tanpa takut membuat kesalahan, membantu mereka dalam memahami materi teks deskriptif, dan meningkatkan penguasaan tata bahasa mereka. Hasil penelitian ini menunjukkan bahwa penggunaan strategi Think-Talk-Write efektif dalam meningkatkan kemampuan siswa dalam menulis teks deskriptif.